Trends and Patterns of Disparities in Burden of Lung Cancer in the United States, 1974-2015 - Zhong, Yu Jie; Wen, Yi Feng; Wong, Hai Ming; Yin, Guosheng; Lin, Ruitao; Yang, Shuan Ying (Frontiers in Oncology, 2019)
Background: Although lung cancer incidence and mortality have been declining since 1990s, the extent to which such progress has been made is unequal across population segments. Updated epidemiologic data on trends and patterns of disparities are lacking. Methods: Data on lung cancer cases and deaths during 1974-2015 were extracted from Surveillance, Epidemiology, and End Results program. Age-standardized lung cancer incidence and mortality and their annual percent changes were calculated by histologic type, demographic variables, and tumor characteristics. Results: Lung cancer incidence decreased since 1990 (1990-2007: annual percent change, -0.9 [95% CI, -1.0%, -0.8%]; 2007-2015: -2.6 [-2.9%, -2.2%]). Among adults aged 20-39 years, higher incidence was observed among females during 1995-2011, after which faster decline in female lung cancer incidence (males: -2.5% [-2.8%, -2.2%]; females: -3.1% [-4.7%, -1.5%]) resulted in lower incidence among females. White population had higher incidence than black population for small cell carcinoma since 1987. Black females were the only group whose adenocarcinoma incidence plateaued since 2012 (-5.0% [-13.0%, 3.7%]). Higher incidence for squamous cell carcinoma was observed among black males and females than among white males and females during 1974-2015. After circa 2005, octogenarians and older constituted the group with the highest lung cancer incidence. Incidence for localized and AJCC/TNM stage I lung cancer among octogenarians and older plateaued since 2009 while mortality continued to rise (localized: 1.4% [0.6%, 2.1%]; stage I: 6.7% [4.5%, 9.0%]). Conclusions: Lung cancer disparities prevail across population segments. Our findings inform effective approaches to eliminate lung cancer disparities by targeting at-risk populations.